2016
DOI: 10.1371/journal.pone.0167299
|View full text |Cite|
|
Sign up to set email alerts
|

Individual Differences in Emotion Regulation, Childhood Trauma and Proneness to Shame and Guilt in Adolescence

Abstract: Dispositional shame and guilt have been associated with psychopathology and an increasing number of studies have traced this relation back to adolescence. This developmental period is thought to be characterized by maturational changes in emotion regulation, which also play an important role in vulnerability to psychopathology, but little is known about the links between emotion regulation and dispositional shame and guilt. The current study investigated the relations between individual differences in the habi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 52 publications
1
17
0
4
Order By: Relevance
“…If, at a later time, the person feels as though they are in a dominant situation, the amygdala can shift into a blame response. This shame/blame processing can reflect a person who freezes in response to abuse in one situation (shame) and becomes the abuser (blame) in a similar situation that triggers the response (Cozolino, 2006; Gold, Sullivan, & Lewis, 2011; Stuewig, Tangney, Heigel, Harty, & McKloskey, 2009; Szentagotai-Tatar, & Miu, 2016; Thomason et al, 2015). To what extent can one say the person committing the crime that gets them incarcerated is not displaying posttraumatic stress behavior?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If, at a later time, the person feels as though they are in a dominant situation, the amygdala can shift into a blame response. This shame/blame processing can reflect a person who freezes in response to abuse in one situation (shame) and becomes the abuser (blame) in a similar situation that triggers the response (Cozolino, 2006; Gold, Sullivan, & Lewis, 2011; Stuewig, Tangney, Heigel, Harty, & McKloskey, 2009; Szentagotai-Tatar, & Miu, 2016; Thomason et al, 2015). To what extent can one say the person committing the crime that gets them incarcerated is not displaying posttraumatic stress behavior?…”
Section: Discussionmentioning
confidence: 99%
“…Understanding how childhood trauma is displayed in adults offers a better way to understand and treat adult behavioral disorders. It potentially can offer a way to better understand the psychotic spectrum (Szentagotai-Tatar, & Miu, 2016;Yen et al, 2002), intergenerational violence (Craig & Sprang, 2007;Langhinrichsen-Rohling, 2005), childhood bullying (Wolke, Copeland, Angold, & Costello, 2013), and criminal behavior (Salmond et al, 2011;Veer et al, 2015).…”
mentioning
confidence: 99%
“…eine Ursache für die Entwicklung einer Depression darstellen, wenngleich bisher vorliegende Forschungsbefunde auf solche negativen Effekte von Schuldgefühlen nur zum Teil oder nur unter bestimmten Voraussetzungen (z. B. nur für Schuldgefühle im Zusammenhang mit Schamgefühlen oder nur für obsessiv erlebte, eine Person gedanklich stark beschäftigende Schuldgefühle) hindeuten [29][30][31][32].…”
Section: Zusammenhang Zwischen Der Angabe Von Im Lebensverlauf Empfundenen Schuldgefühlen Und Alter Geschlecht Bildung Und Aktuellem Deprunclassified
“…Indeed, study after study has shown that guilt is significantly linked to moral behaviour and cooperation whereas shame is not (De Hooge, Zeelenberg, & Breugelmans, 2007;Tangney & Dearing, 2002). Further guilt and it has low or no association with mental health problems (Gilbert, 2000c;Tangney & Dearing, 2002;SzentaÂgotai-Tȃtar, & Miu, 2016). In contrast, shame proneness, when rooted in a deep sense of an unattractive and an undesired self, is often associated with hostile forms of self-criticism and is linked to whole range of psychopathologies (Gilbert, 2009).…”
Section: Guiltmentioning
confidence: 99%